Perceptions towards rooftop gardens as alternative to open green spaces among residents in Sulaymaniyah City, Kurdistan - Abdulrahman, Lamia Karim (2014)
Rapid urban development has caused shortage of open green spaces in Sulaymaniyah, Iraq. This has created many problems to city residents and visitors such as lack of recreational spaces, formation of urban heat island and loss of tourism revenues. Creating new green spaces is not quite favourable due to the high cost of land in the city. Creating green areas on rooftops such as a rooftop garden is a potential alternative that requires investigation. This study aims to discover the views of public officials and residents of Sulaymaniye regarding developing rooftop gardens as a viable alternative to increase green open spaces in the city. This research surveyed 60 public city officials (architects, engineers, city planners and city administrators) on their awareness of rooftop gardens and their potential in increasing green open spaces. This was followed by a visual preference survey of 391 residents of Sulaymaniyah. Respondents were asked about their preferences for different forms (Formal, Informal, Naturalistic and Productive) of rooftop gardens as well as their willingness to support the development of rooftop gardens. Finally, indepth interviews were done with 21 city officials to examine their views of rooftop gardens as a means to increase green outdoor spaces in the city. Results indicated that the majority of Sulaymaniyah public officials were aware of developing rooftop gardens as a strategy to overcome the lack of green outdoor spaces in Sulaymaniyah. In addition, city residents indicated that they preferred roof gardens as a strategy to overcome diminishing green open spaces in the city, and that they would support the initiative. Furthermore, the Informal Rooftop Garden type was the most preferred while the Productive Rooftop Garden type was the least preferred among the residents. The findings of this study may contribute to the discovering of solutions to the problem. This information is useful to the city planners and administrators as their knowledge on what the residents prefer for their rooftop gardens and the residents’ willingness to support the effort will help them to make future plans or decisions in solving the problem.